Maximizing teacher performance and student learning outcomes through creative management principles - Corry Yohana; Ratna Tri Hari Safariningsih; Rizki Firdausi Rachma Dania; Shaierah Gulabdin (Special Casting and Nonferrous Alloys, 2024)
To maximize teacher performance and student learning outcomes, creative management from the principal is needed to support development and innovation to improve the quality of education. To maximize teacher performance and student learning outcomes under the creative leadership of school principals at the elementary to high school and/or vocational levels in Jakarta, Bogor, Tangerang, Depok, and Bekasi (Jabodetabek). This study analyzes factors like critical thinking, collaboration, vision, emotional intelligence, and environment. Respondents in this study consisted of 200 educators selected by convenience sampling method, with sampling using the Krijcie Morgan method. Data was collected using discussion methodsand the distribution of online questionnaires to respondents. The study was conducted using quantitative methods. Data analysis was performed using AMOS. This study demonstrates that teacher effectiveness and student learning outcomes are positively impacted by the principal's managerial ability, which is also favorably influenced by the school's environment, emotional intelligence, school vision, and critical thinking abilities.